Tingkat Kepuasan Pengunjung terhadap Fasilitas Olahraga Rekreasi Renang di Kolam Renang Tirta Indah Kabupaten Kediri - Faza Dhi’fan Wicaksono; Catur Supriyanto; Made Pramono; Lutfhi Abdil Khuddus (Mutiara Pendidikan dan Olahraga, 2025)
Visitor satisfaction is very important to improve the quality of the swimming pool. Keeping the pool clean and improving facilities such as bathrooms and water cleanliness are the drivers of visitor satisfaction. Based on the survey results, it was found that the lack of cleanliness of the swimming pool was due to a lack of self-awareness on the part of visitors to maintain cleanliness and notification from the pool. The purpose of this study was to determine the level of satisfaction of visitors to Tirta Indah Swimming Pool, Kediri Regency, East Java. The type of research used is descriptive quantitative using purposive non random sampling with a sample of 80 people. The research instrument used a questionnaire sheet. This data collection uses questionnaire results and officer interviews. Data analysis techniques using descriptive statistical analysis. Data processing using editing and tabulating. The results showed that the level of visitor satisfaction with swimming recreation sports facilities at Tirta Indah Swimming Pool, Kediri Regency was classified as satisfactory, in the product quality category of 75.25%, price category of 80%, service quality category of 83.75%, emotional factor category of 63.75%, and convenience category of 81.25%. The conclusion related to the research is that the majority of visitor satisfaction at Tirta Indah Swimming Pool is categorized as satisfactory, partly satisfactory because many of the respondents are satisfied from the category of swimming pool ticket prices which are relatively cheap and most respondents are not satisfied because the prices of food and drinks in the swimming pool canteen are expensive.